2020
DOI: 10.1167/tvst.9.9.34
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quantitative Index of Meibomian Gland Dysfunction, the Meibomian Gland Tortuosity

Abstract: To quantitatively measure meibomian gland (MG) tortuosity in meibomian gland dysfunction (MGD) patients and normal controls and to observe the efficacy of evaluating MG tortuosity for the diagnosis of MGD. Methods: This cross-sectional study enrolled 32 obstructive MGD patients and 28 normal volunteers. Clinical assessments were performed, including symptom questionnaires, tear meniscus height, tear break-up time (TBUT), corneal fluorescein staining, lid margin abnormality, MG expressibility, and meibography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…Studies involving the presence of gland tortuosity or degrees of the most bent gland have suggested a correlation between tortuosity and MGD, lid margin scores, meiboscores, meibum expressibility scores, and TBUT, demonstrating the clinical importance of identifying patients with significant gland tortuosity. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies involving the presence of gland tortuosity or degrees of the most bent gland have suggested a correlation between tortuosity and MGD, lid margin scores, meiboscores, meibum expressibility scores, and TBUT, demonstrating the clinical importance of identifying patients with significant gland tortuosity. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, we also found a correlation between the severity of meibomian gland atrophy and tortuosity (p <0.001). 8 , 11 Currently, the mechanism of association between gland atrophy and tortuosity is not fully understood. Additionally, as gland atrophy grades become higher there are fewer glands to assess for tortuosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic MGD has been documented as a preclinical stage of MGD with clinical changes but without lid-related symptoms [36]. Using this MGs analysis method, our team found in earlier study that MG tortuosity was significantly higher in asymptomatic MGD subjects than in normal controls and that MG tortuosity showed a significant correlation with TBUT, lid margin score, meiboscore, and meibum expressibility score [37]. Based on these findings, MG tortuosity may serve as a good index for diagnosing MGD.…”
Section: Discussionmentioning
confidence: 83%
“…In our ndings, there was also a statistically signi cant positive correlation of the presence of tortuous glands in the UL with a better initial and average NIKBUT. Since we focus on subjects with evaporative dry eye and that in the new DEWS II 1 report the use of the Schirmer test is not suggested, we did not carry out this study so we cannot corroborate the nding described by Daniel et al 19 Other studies have reported other morphological alterations, in patients with dry eye and other ocular surface diseases, Mathers et al suggest that that MG distortion is the rst-stage morphological alteration that occurs in MG. 20 Lin et al 21 reported that the average tortuosity of all MGs was signi cantly increased in the MGD group compared to the normal controls, and higher in the symptomatic MGD patient group compared to the asymptomatic MGD patient group. MG tortuosity has been associated with contact-lens wear and more commonly observed in Caucasians.…”
Section: Discussionmentioning
confidence: 99%